Work Analytic Tools: Needs Assessment Tools for HPT Professionals. Issue 2 (10th February 2019) - Langdon, Danny G.; Langdon, Kathleen M.
Abstract: This article presents the addition of work analytic tools (WATs) to the performance technologist's tool kit. These tools apply the language‐of‐work formula (developed, tested, and published in various forums over the past two decades) to achieve an array of performance improvement solutions. Using these WATs changes our role from conductor of analysis to facilitator of solution. As a result, clients become more committed to the solutions they themselves define and must solve, implement, and measure for effectiveness.